Secrets of Japan : - Lal, Chaman (Kenkyusha Printing Co., 1935)
A good solid copy with sticker residue on spine and stamp from the "Library of S. S. Taiyo Maru" on endpapers and title. First edition. Cloth. 8vo. xii, 224 pp.; xxx [adv]. Illus. with 48 b/w photos. Cover title is "Secrets of Japan Through Indian Eyes." Interesting item from the Library of the S. S. Taiyo Maru, a Nippon Yusen Kaisha (NYK) liner. She was sunk in 1942 by the submarine USS Grenadier.